Dampak Transformasi Digital Terhadap Kinerja Karyawan UMKM di Era Disrupsi - Wijaya, Reni; Basri, Syukrial; Ming, Su Wei (Pustaka Galeri Mandiri, 2026)
The era of disruption requires Micro, Small, and Medium Enterprises (MSMEs) to transform digitally to maintain their existence. This study aims to analyze the impact of digital transformation on MSME employee performance in Pariaman City. This research uses a quantitative approach with linear regression analysis. The sample consists of 100 MSME actors selected using a purposive sampling technique. Data were analyzed using SPSS 26. The results of the study show that digital transformation has a positive and significant effect on employee performance with a significance value of 0.000 < 0.05. The regression coefficient of 0.396 indicates that every increase in digital transformation implementation will improve employee performance. The R-Square value of 0.215 indicates that digital transformation contributes 21.5% to the variance of employee performance, while the rest is influenced by other factors. This study concludes that digital adoption is no longer a choice but a necessity to improve work efficiency and productivity in facing market disruption.